THE EFFECT OF LIMITED DIRECT LEARNING SYSTEM DURING COVID-19 ON STUDENT LATHE COMPETENCY TEST RESULT - Sujadi Sujadi; Sandi Setiawan; Mumu Komaro; Purnawan Purnawan (Journal of Mechanical Engineering Education, 2022)
The Covid-19 pandemic has become a global pandemic, it has an impact on the education. Direct learning system suddenly could not be implemented because suppressing the spread of the virus. Based on the joint decree of four ministers regarding guidelines for the implementation of learning system during the Covid-19 pandemic, limited direct learning is carried out. This study aims to determine the effect of the implementation of limited direct learning on the results of the lathe machining competency test. This research uses a quantitative descriptive approach and documentation studies. The instruments that used in this study are form of observation sheets of competency test results and sheet of assessment of competency test from partner industry. The result of this study showed that the implementation of limited direct learning has a positive impact to the result of lathe competency test obtained by student. The results showed that the implementation of limited direct learning had a positive impact on the results of student competency test, as evidenced by competency test scores by using the categories such as SK (sangat kompeten), K (kompeten), CK (cukup kompeten), and BK (belum kompeten). The scores obtained by students with their respective percentages are as much as 2%, 82%, 16%, and 0%.